A clinico-morphological study of glandular hyperplasias of uterine cervix - B. J., Naveen Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Non neoplastic lesions of uterine cervix form a major bulk of the Diagnosis in histopathological departments. Some of the non-neoplastic lesions of uterine cervix mainly exuberant processes like glandular hyperplasias are prone to varying extents of misinterpretation. This can lead to potentially adverse consequences for the patient in the form of inappropriate treatment. But, studies on non-neoplastic lesions are comparatively less. This is an attempt to study the clinico morphologic features of glandular hyperplasias of uterine cervix. Methods: The present study is a retrospective study conducted using histopathology records of 2years (June 2013 to May 2015) in the department of Pathology, at a tertiary care hospital in south India. The study included 811 specimens of uterine cervix obtained either in the form of biopsies or hysterectomy specimens Results: 44 cases of Glandular hyperplasias of uterine cervix were encountered in the present study. In the present study uterine cervix is the most frequently occurring lesion, seen in 20 (2.47%) cases, followed by Microglandular hyperplasia in 13 (1.6%), Diffuse laminar endocervical glandular hyperplasia in 7 (0.86%), and Florid deep glands in 4 (0.49%). Conclusions: Glandular hyperplasias of uterine cervix arise in the reproductive age. Early age of occurrence in the present study compared to other studies can be attributed to early marriages and childbearing in Indian women. As diagnosis rests on histologic characteristics in routinely stained sections, familiarity with these lesions by pathologists is essential to avoid over diagnosis and treatment.